СHALLENGES FACED BY STUDENTS IN THE DEVELOPMENT OF ORAL SPEECH IN ENGLISH AND THEIR EFFECTIVE SOLUTIONS (SCIENCE TIME JOURNAL, 2026)
This article is devoted to examining the core challenges language learners face when developing oral speech skills in English within higher education, specifically focusing on the context of Uzbekistan. While many students exhibit strong grammatical knowledge and reading comprehension, oral communication remains a significant hurdle. Drawing upon the prominent frameworks of Elaine K.Horwitz's "Foreign Language Anxiety" and Scott Thornbury's balance of fluency and accuracy, this paper analyzes the underlying psychological and linguistic barriers. Furthermore, the article proposes practical, innovative pedagogical methods and communicative approaches aimed at reducing anxiety and fostering balanced oral proficiency.